Anti-cancer, Anti-inflammatory, Cytotoxic and Biochemical Activities of a Novel Phosphonotripeptide Synthesized from Formyl Pyrazolofuran using TUBU as Condensing Agent - H. Ouf, Nabil; A.Hamed, Mohamed; El Sayed, Ibrahim; Sakran, Mohamed Ibrahim (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
A novel and mild protocol for the synthesis of phosphonotripeptide 16 were achieved from novel formylpyrazolofuran 3, benzyl carbamate 5, triphenyl phosphite 6 by Birum-Oleksyszyn reaction using copper (II) trifliate as Lewis acid catalyst in dry dichloromethane at room temperature which synthesis of novel N-benzyloxy-Î±-aminophosphonate 7 . A mechanism for this condensation reaction is proposed. Cleavage of the N-benzyloxy carbonyl group under acid hydrolysis afford the free Î±-aminophosphonate 9 in quantitative yield. This in turn, by reaction with N-phthaloylglycine 12 via TUBU to phthalimido group 13.Cleavage of phthalimido group under hydrazinedihydrochloride afford free peptide 14 .the result phosphonotripeptide 16 obtained by the reaction of free peptide with bioactive cyclic moiety-COCl 15. The structures of all new compounds were established by IR,1HNMR and mass spectral data. Also anti-cancer, anti-inflammatoryÂ  and biochemical activities of all these compounds were reported.